Structural Changes in Estonian Manufacturing and Regional Development - Grigori Fainstein (European Regional Science Association (ERSA), 2006)
In the transition to a market economy the countries of Eastern Europe underwent a significant structural changes. There is a plenty of literature on the structural changes in industry in transition countries. Some works on industrial restructuring have appeared in Estonia as well. By now the time series of data on this field are long enough to conduct this kind of analysis in a more systematic and formal way. The aim of this work is an analysis of the structural changes in the Estonian manufacturing in transition and it relation with regional development. The changes in manufacturing output structure is analyzed by the NACE classification broad sectors. Changes in values and real output are considered. The development of relative prices, industrial employment and labor productivity are also examined. A set of indices are calculated to study regional manufacturing dynamics. After that econometric analysis of relation between industrial restructuring and the regional development is considered. The paper ends with the conclusions.
Keywords: 330